Multidimensional school features associated with physical activity among youth at risk of obesity: an exploratory principal component and generalized estimating equation analysis - Madeleine Bird; Tracie A. Barnett; Daniel Fuller; Deanna Chinerman; Marie-Ève Mathieu; Geetanjali D. Datta (BMC, 2023)
Abstract Background Schools may be high-leverage points for the promotion of physical activity (PA), yet little is known about school built and social environments among youth at high risk of obesity. Purpose To characterise school built and social environments that may be salient for PA and to examine associations between school PA environments and PA in youth at risk of obesity. Methods Data from youth attending 206 schools (314 youth in 2005-2008, and 129 youth in 2008-2010) within the QUALITY cohort study, a longitudinal investigation of youth at high risk of obesity were used. Features of schools, based on built, policy/programming and social environments were identified using principal components (PC) analysis. Gender-stratified generalized estimating equation (GEE) models were used to explore associations between school features and accelerometer measured mean counts per minute (MCPM), mean daily moderate-to-vigorous physical activity (MVPA) and the odds of meeting MVPA guidelines cross-sectionally and prospectively using 90% confidence intervals. Results Nine PCs were identified. Associations were observed between PA and 7 of the 9 PCs. The social environment seemed to be particularly important. Social Norms to Promote PA was associated with an increase in girls' baseline MCPM and MVPA. High Willingness to Promote PA was associated with boys' MCPM, MVPA, and odds of meeting MVPA guidelines, at both baseline and follow-up. Conclusion School built and social contexts may be associated with PA cross-sectionally and over time. Further studies are necessary to confirm the direction and magnitude of effects and to establish their relevance to school-based health promotion efforts.